Réponses

2014-09-17T19:17:31+02:00
A = - 4/3 + 5/6
A = - 4 x 2 / 3 x 2 + 5/6
A = - 8/6 + 5/6
A = - 3/6
A = 3 x - 1 / 3 x 2
A = - 1/2

B = - 7/3 - 5/12
B = - 7 x 4 / 3 x 4 - 5/12
B = - 28/12 - 5/12
B = - 33/12
B = 3 x - 11 / 3 x 4
B = - 11/4

C = - 3/25 - -2/5  (je ne sais pas si les 2 - sont faits exprès ?)
C = - 3/25 + 2/5
C = - 3/25 + 2 x 5 / 5 x 5
C = - 3/25 + 10/25
C = 7/25

Au cas où :

C = - 3/25 - 2/5
C = - 3/25 - 2 x 5 / 5 x 5
C = - 3/25 - 10/25
C = - 13/25

D = 3/4 - 6/5
D = 3 x 5 / 4 x 5 - 6 x 4 / 5 x 4
D = 15/20 - 24/20
D = -9/20